A new species of Orybina Snellen, 1895 from India (Lepidoptera, Pyralidae, Pyralinae) - Singh, Navneet; Ranjan, Rahul (Zootaxa, 2018)
The genus Orybina Snellen, 1895, a member of tribe Pyralini of the subfamily Pyralinae and family Pyralidae, was established as the objective replacement name for Oryba Walker, 1863. The original genus Oryba was established for its type species Oryba flaviplaga Walker, 1863 (by monotypy) from North Hindostan [North India]. Recently, the genus is reviewed by Qi et al. (2017) with inclusion of eight species and one subspecies in the World: Orybina kobesi Roesler, 1984, Orybina plangonalis (Walker, 1859), Orybina regalis (Leech, 1889), Orybina bellatulla Qi & Li, 2017, Orybina puerensis Qi & Li, 2017, Orybina hoenei Caradja, 1935, Orybina flaviplaga (Walker, 1863), Orybina imperatrix Caradja, 1925 and Orybina flaviplaga kiangsualis Caradja, 1925. The genus can be diagnosed by the rosteriform labial palpi, forewings reddish-brown or saffron, with a yellow spot (except in Orybina bellatulla). In the male genitalia uncus is triangular or tongue-shaped, and valvae are enlarged apically. In the female genitalia, the anterior apophyses and posterior apophyses are short, the ductus bursae usually coiled anteriorly, and the ovate corpus bursae is without signum (Qi et al. 2017).